Genetic determinants of glutamine synthetase in Drosophila melanogaster: a gene for glutamine synthetase I resides in the 21B3-6 region. - Caggese, C.; Caizzi, R.; Bozzetti, M.P.; Barsanti, P.; Ritossa, F. (Biochemical Genetics, 1988)
Recombinational and deletion mapping of electrophoretic variants of the glutamine synthetase I isozyme (GSI) in Drosophila melanogaster locates the gene in the 21B region on the second chromosome. We have conducted a genetic analysis of the region extending cytologically from 21A to 21B4-6. Recessive lethal mutations were generated by ethyl methanesulfonate (EMS) and ethyl nitrosourea (ENU) mutagenesis and by hybrid dysgenesis (HD). These lethals fall into seven functional groups, which were partially ordered by complementation with cytologically defined deficiencies of this region generated by hybrid dysgenesis. Two of the EMS- and two of the ENU-induced lethals fulfill biochemical criteria expected for null alleles of the GSI gene.